WhatsApp Group 'Bantul in Hong Kong': Communication Platform of Indonesian Migrant Workers during Covid-19 Pandemic in Hong Kong - Muntadliroh, nfn; Rahmawati, Nila (Jurnal Pekommas, 2020)
Communication is an important aspect for Indonesian Migrant Workers' survival (PMI) in Hong Kong during the Covid-19 pandemic. In a crisis and uncertain situation, PMI from Bantul in Hong Kong communicate using the WhatsApp group "Bantul in Hong Kong" to stay connected with their partners. For this reason, this research aims to describe the motives of using the WhatsApp group "Bantul in Hong Kong" by PMI during the Covid-19 pandemic. This research employed qualitative case study approach. The Data was collected using in-depth interviews towards the WhatsApp group members which was selected by snowball sampling. The results showed that the motives of using WhatsApp group "Bantul in Hong Kong" were: social interaction, information seeking, entertainment, relaxation and comfort, sharing information, monitoring the other, and growing of communication empathy. In addition, the use of this platform also has negative effects such a communication irritation to group members.